Coping and help in birth: An investigation into 'normal' childbirth as described by new mothers and their attending midwives. (September 2016) - Darra, Susanne; Murphy, Fiona
Abstract: Objective: to investigate how 'normal' childbirth is described by new mothers and their attending midwives. Design: a qualitative, reflexive, narrative study was used to explore birth stories using in-depth, un-structured interviews. Setting: 21 new mothers and their 16 attending midwives were recruited from the locality surrounding a district general hospital in South Wales, United Kingdom (UK). Findings: the findings identified that the mothers wanted to cope with labour and birth, by breathing through it and using some birth interventions with the help of knowledgeable midwives. Midwives aimed to achieve 'normality' in birth but also commonly utilised birth interventions. Consequently the notion of 'normal' birth as not involving interventions in birth was not found to be a useful defining concept in this study. Furthermore, current dichotomous models and theories of birth and midwifery in particular those relating to pain management did not fully explain the perspectives of these women and their midwives. Implications for practice: dichotomous models and theories for birth and midwifery practice and those which incorporate the term 'normal' birth are shown to be not entirely useful to fully explain the contemporary complexity of childbirth in the UK. Therefore it is now necessary to consider avoiding using dichotomous models of birth and midwifery in the UK and to instead concentrate on developing integrated models that reflect the real life current experiences of women and their midwives. Highlights: Women want to cope with labour and birth with the help of knowledgeable midwives. They want to do this by breathing and using some birth interventions. Midwives aim for normal birth but commonly utilise birth interventions especially to manage pain. Normal' birth is not a useful defining concept. Dichotomous birth and midwifery models do not fully explain the perspectives of women or midwives. Current dichotomous models and theories relating to birth and midwifery, separating the normal from the abnormal and non-intervention from intervention, do not fully explain the perspectives of women or their midwives.